Sistem Pendukung Keputusan Penentuan Pembimbing Skripsi Menggunakan Metode Analytical Hierarchy Process - Cahyono, Hendri Adi; , Husni Thamrin, S.T, M.T, Ph.D (2016)
Thesis is the final project lesson for students S1. Prodi informatics Muhammadiyah University of Surakarta in the manufacturing thesis stage first thing to do is manufacture a title and determination thesis mentor. In determining the thesis mentor in the Prodi informatics still use manual way, and usually require a long time. Because must meeting lecture which one is match the titles and descriptions of students who pretty much. In this meeting the lecturer should also read the title and description of each student to really match with faculty expertise and experience lecturer in guiding. Meetings can take time one day work for determine mentor for 50 students, then this is very inefficient. In this research the authors have made a decision support system thesis mentor determination is made by using the method analytical hierarchy process (AHP). This application can determine thesis mentor appropriate title of student quickly and accurately. Based on the research results of the application of decision support system thesis mentor determination using method analytical hierarchy process (AHP) can be concluded that this application allows the bureau thesis and study program informatics for election thesis supervisor with accuracy applications 53.8%.